Essays on political economy and institutions - Stein, Guilherme (2016)
This thesis presents two theoretical models. The first shows how the cost of doing business associated with red tape arises as a response to institutional failure, namely, a failure of the legal system. It shows that, when legal system is inefficient, an increase in the cost of doing business can increase society’s welfare. The second model shows how credit constraints affect political preferences of the society relating to human capital investments. Families that are credit constrained invest less in their offspring human capital and thus also prefer policies that involve direct cash transfers to human capital investments.